Analisis Penggunaan Bahasa Baku Dan Nonbaku Terhadap Kehidupan Sehari-Hari Generasi Milenial Di Kota Medan - Gresia Septina Sitohang; Frandika Situmorang; Eza Syahbana; Radja Marihat Batubara; Fitriani Lubis (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The widespread use of standard and non-standard languages ​​among society is very problematic. Many members of society, especially students or the millennial generation, make mistakes in pronouncing it incorrectly. This research method uses qualitative or descriptive methods. It is hoped that using this method will provide an overview of the use of standard and non-standard language among the millennial generation in the city of Medan. The data sources obtained are based on research results and journal literature studies. The data collection technique used was in the form of randomly distributing questionnaires to the millennial generation. Based on the results of the questionnaire obtained from the younger generation in the city of Medan as many as 34 respondents, it can be explained that the results obtained were 8 respondents or 23.5% who chose the frequent option and 26 respondents or 76.5% of the total respondents chose the infrequent option , this proves that there are still many millennial generations who are reluctant to use standard language in their daily conversations. It can be concluded that there are still many millennial generations who are reluctant to use standard language in their daily conversations. Millennials also tend to predominantly use non-standard languages ​​compared to standard languages.